Peran Pemerintah Daerah Dalam Mengontrol Harga Pangan Berdasarkan UU Pangan No. 18 Tahun 2012 Pasal 55 (Perspektif Ekonomi Islam) - Murdiansah S. A. Karim (Univiversitas Dr. Djar Wattiheluw, 2020)
The purpose of this research is to examine the role of local government, especially the city government of Tidore Islands, to stabilize food prices based on Food Law No. 18 of 2012 article 55 in the perspective of Islamic economics. This type of research is classified as qualitative research by presenting the direct relationship between the author and the respondent. In data collection techniques carried out include observation, interviews, and documentation, so that the authors conducted interviews with respondents including the Tidore City government and the tomato farmers of Gurabunga Village. In this study, the authors found that the role of regional government in managing food prices, local government not only controls one sector but the role of local government also controls the distribution of supply prices from farmers to the market without going through the collectors (middlemen).